Effects of polymorphism in G2677T/A triallelic region of MDR1 gene in Turkish patients with inflammatory bowel disease - Ayşegül SAPMAZ; Senem Ceren KARATAYLI; Ülkü DAĞLI; Zeki Mesut Yalın KILIÇ; Murat TÖRÜNER; Yasemin ÇELİK; Muhip ÖZKAN; İrfan SOYKAN; Hülya ÇETİNKAYA; Aysel ÜLKER; Ali ÖZDEN 0; A. Mithat BOZDAYI (Turkish Journal of Gastroenterology, 2019)
-